An insight into microstructural evolution during plastic deformation in AA6061 alloy after friction welding with alumina-YSZ composite. (December 2015) - Uday, M.B.; Ahmad-Fauzi, M.N.; Noor, Alias Mohd; Rajoo, Srithar
Highlights: Plastic deformation of FW for AA6061 alloy/alumina-YSZ composite were clarified. Different technique analyses were used to study the plastic deformation in the metal. Microstructure, microhardness and grain size of AA6061 alloy after joint were estimated. The grain structure and dislocation density of AA6061 alloy also were evaluated. The results showed different deformation mechanisms at different speeds and locations. Abstract: The microstructural studies of friction welding help in understanding microstructural changes occurred during friction welding. The effect of plastic deformation on microstructural changes in AA6061 alloys is the subject of the considerable practical interest. The development of this subject is remarkable, but a more detailed study could lead us to have a better understanding of the phenomenon. In the present study, Optical Microscopy (OM), Field Emission Scanning Electron Microscopy (FESEM), microhardness and X-ray diffraction (XRD) were used to study the effect of plastic deformation on the grain structure and dislocation density of AA6061 alloy when there was a joint, with the ceramic. The effect of rotation speed and the degree of deformation appeared to be higher on the AA6061 alloy than on the ceramic part. Results showed different deformation mechanisms at different rotational speeds and confirmed unambiguously the change in grain size, microhardness, crystalline grain and dislocation density as a result of changing the distances from the interface.